The Influence of CSR Financial Management Effectiveness on SROI Value with Reporting Transparency as a Moderating Variable - Dini, Maya; Hamzah, Amir; Amaliah, Ima; Nurhayati, Nunung (Yayasan Gema Bina Nusantara, 2026)
This study aims to examine how the Effectiveness of Corporate Social Responsibility (CSR) Financial Management contributes to increasing the Social Return on Investment (SROI) value, as well as to assess the role of GRI-based Reporting Transparency as a moderating variable that strengthens this relationship. The research was conducted on companies that implement CSR programs sustainably, using a quantitative approach with a sample of 30 respondents involved in CSR management and reporting. Data were collected through standardized questionnaires and processed using multiple linear regression accompanied by a moderation test to determine whether transparency provides a strengthening effect. The results of the study show that the effectiveness of CSR financial management has a significant influence on SROI value, meaning that the better the planning, budgeting, implementation, and evaluation processes of CSR finances, the greater the social benefits generated compared to the costs incurred. In addition, reporting transparency based on GRI standards is proven to strengthen this relationship. When information is presented honestly, comprehensively, and in a traceable manner, stakeholder trust increases, making the social impact produced more visible and measurable. These findings emphasize the importance of professional CSR financial management and transparent reporting practices as the foundation of sustainability accountability. This study also provides a basis for future research to explore other variables, such as governance quality, community participation, or social innovation, that may influence SROI values across various sectors.